Show that the partial differential equations
z = px + qy and 2xy(p2 + q2) = z(yp + xq)are compatible
Two PDEs f,gf,g are compatible if they have a common solution. We must show that,
"[f,g]=\\frac{\\partial (f,g)}{\\partial (x,p)}+p\\frac{\\partial (f,g)}{\\partial (z,p)}+\\frac{\\partial (f,g)}{\\partial (y,q)}+q\\frac{\\partial (f,g)}{\\partial (z,q)}=0"
z=px+qy
Let f=z−px−qy=0
2xy(p^2+q^2)=z(yp+xq)
Let g=2xy(p^2+q^2)-z(yp+xq)=0
"\\frac{\\partial f}{\\partial x}=-p,\\frac{\\partial f}{\\partial y}=-q,\\frac{\\partial f}{\\partial z}=1,\\frac{\\partial f}{\\partial p}=-x,\\frac{\\partial f}{\\partial q}=-y\\\\ \\frac{\\partial g}{\\partial x}=2y(p^2+q^2)-zq,\\frac{\\partial g}{\\partial y}=2x(p^2+q^2)-zp,\\frac{\\partial g}{\\partial z}=-(yp+xq),\\frac{\\partial g}{\\partial p}=4xyp-yz,\\frac{\\partial g}{\\partial q}=4xyq-xz."
"\\frac{\\partial (f,g)}{\\partial (x,p)}=\\begin{vmatrix} \\frac{\\partial f}{\\partial x} & \\frac{\\partial g}{\\partial x} \\\\ \\frac{\\partial f}{\\partial p} & \\frac{\\partial g}{\\partial p} \\end{vmatrix}=\\begin{vmatrix} -p & 2y(p^2+q^2) \\\\ -x & 4xyp-yz \\end{vmatrix}=2xyq^2+yzp-2xyp^2"
"\\frac{\\partial (f,g)}{\\partial (z,p)}=\\begin{vmatrix} \\frac{\\partial f}{\\partial z} & \\frac{\\partial g}{\\partial z} \\\\ \\frac{\\partial f}{\\partial p} & \\frac{\\partial g}{\\partial p} \\end{vmatrix}=\\begin{vmatrix} 1 & -(yp+xq) \\\\ -x & 4xyp-yz \\end{vmatrix}=3xyp-yz-x^2q"
"\\frac{\\partial (f,g)}{\\partial (y,q)}=\\begin{vmatrix} \\frac{\\partial f}{\\partial y} & \\frac{\\partial g}{\\partial y} \\\\ \\frac{\\partial f}{\\partial q} & \\frac{\\partial g}{\\partial q} \\end{vmatrix}=\\begin{vmatrix} -q & 2x(p^2+q^2) \\\\ -y & 4xyq-xz \\end{vmatrix}=2xyp^2+xzq-2xyq^2"
"\\frac{\\partial (f,g)}{\\partial (z,q)}=\\begin{vmatrix} \\frac{\\partial f}{\\partial z} & \\frac{\\partial g}{\\partial z} \\\\ \\frac{\\partial f}{\\partial q} & \\frac{\\partial g}{\\partial q} \\end{vmatrix}=\\begin{vmatrix} 1 & -(yp+xq) \\\\ -y & 4xyq-xz \\end{vmatrix}=3xyq-xz-y^2p"
"f,g]=2xyq^2+yzp-2xyp^2+3xyp^2-yzp-x^2pq+2xyp^2+xzq-2xyq^2+3xyq^2-xzq-y^2pq\\\\ [f,g]=3xyp^2+3xyp^2-x^2pq-y^2pq\\\\ [f,g]=4xyp^2+4xyq^2-xyp^2-x^2pq-xyq^2-y^2pq\\\\ [f,g]=4(xy(p^2+q^2))-xp(yp+xq)-yq(xq+yp)\\\\ [f,g]=2z(xp+yq)-(xp+yq)(yp+xq) \\text{ From (2)}\\\\ [f,g]=2z(xp+yq)-z(yp+xq) \\text{ From (1)}\\\\ [f,g]=z(yp+xq)\\neq0" Hence,f,g are not compatible.
Comments
Leave a comment